Aggregation-induced emission of 5-(benzylidene)pyrimidine-2,4,6-triones - Mendigalieva, S.S.; Birimzhanova, D.A.; Irgibaeva, I.S.; Barashkov, N.N.; Sakhno, Y.E. (KU Publ., 2022)
5-(Benzylidene)pyrimidine-2,4,6-triones with different substituents on the phenyl rings: 5-(4’-dimethylaminobenzylidene) barbituric acid and 5-(4’-methoxybenzylidene) barbituric acid were synthesized, and their spectral-luminescent properties were investigated. A decreasing fluorescence efficiency in the solid-state is general and is mainly attributed to the intermolecular vibronic interactions, which induce the nonradiative deactivation process. Whereas the isolated dye molecules are virtually non-luminescent in dilute solutions, they become highly emissive upon solution thickening or aggregation in poor solvents or in the solid-state, show an increase of luminescence intensity, the phenomenon of the aggregation-induced emission (AIE phenomenon). The development of efficient luminescent materials is a topic of great current interest. The emission color is changed from red (maximum at 630 nm) to green (maximum at 540 nm) by varying the substituent on the phenyl ring from dimethylamino to the methoxy group. Theoretical calculation shows that the dye molecules' aggregation-induced emission characteristics result from intermolecular interactions. Utilizing such features, the molecules can be employed as fluorescent probes for the detection of the ethanol content in aqueous solutions.
5-(Бензилиден)пиримидин-2,4,6-триондарының агрегаттық-индукцияланған эмиссиясы
Агрегационно-индуцированная эмиссия 5-(бензилиден)пиримидин-2,4,6-трионов
Keywords: aggregation-induced emission; barbituric acid; fluorescent probes; fluorescence peak intensities; luminophore; dye molecules; substituent phenyl ring; solid state; intramolecular rotations